THE ROLE OF UNIVERSITY IN TEACHERS INITIAL TRAINING: A LOOK AT THE PEDAGOGICAL POLITICAL PROJECT FROM THE MAJOR IN LANGUAGE AND LITERATURE IN A PUBLIC UNIVERSITY - Fernanda Maria Müller Gehring (Travessias, 2015)
In this paper we focus on the Major in Language and Literature from UNIOESTE, campus Marechal Cndido Rondon city, comparing the current Pedagogical Political Project (PPP) and the reformulated one by the board of that campus project which was vetoed by the responsible agencies. By the analysis of PPPs, we observe at what levels have taken the changes and their causes. In addition, we will weave some considerations about the creation process of universities courses in Brazil; we will approach how was the inclusion of educational subjects in teacher training courses, through a historical path of laws and reforms in higher education; we will also approach discussions about the university programs importance with the initial training of teachers. We could verify through the PPPs analysis that there was the intention to improve the training of students from that course, especially by trying to expand hours and by the implementation of pedagogical subjects in the curriculum. The theoretical discussion is based on authors such as Mello (2000), Oliveira, Bonfim (2012), Paiva (2005) and Severino (2012), among others.